Off label use of antimalarials in covid-19 patients (Research, Society and Development, 2020)
This study aimed to verify the level of scientific evidence on the off label use of chloroquine and hydroxychloroquine for the treatment of patients with covid-19 in scientific productions published in renowned international journals. It is an integrative literature review, of an exploratory nature, with a qualitative approach. To compose the corpus of final analysis, 5 articles were selected that met the eligibility criteria established for the study. Through the works highlighted in this article, it is possible to observe that the drugs under study have promising results against covid-19 and can help prevent the progression of the disease to a critical state. It was observed that there were adverse reactions considered mild in two patients being treated with hydroxychloroquine, but no side effects considered serious. Caution is recommended when using these drugs, as they can cause adverse effects.